A multiattribute decision support system with imprecise input and time-dependent modelling. (24th February 2004) - Rios-Insua, Sixto; Jimenez, Antonio; Mateos, Alfonso; Prieto, Tomas
We describe a modelling and problem-solving process supported by a decision support system, which accounts for the possibility of different models depending on factors like multiple conflicting objectives, uncertainty about the consequences of the decisions, imprecision concerning the decision maker's preferences and decisions with consequences that span several time periods. This decision support system addresses all the above aspects, which can be simultaneously taken into account in real decision making problems, by considering an objective hierarchy that models appropriate time preferences. The analysis is focused on judgemental inputs, imprecise scaling factors on objectives and imprecise scalar utility functions on the attributes of the hierarchy for the purpose of aggregation, if appropriate, in a scalar or vectorial global additive utility function, which can incorporate discount factors to evaluate the timestream vectors. The decision support system includes an optimisation method based on the simulated annealing metaheuristic, as well as a multiparametric sensitivity analysis as an aid for identifying the optimal alternative.